2014
DOI: 10.1080/13102818.2014.933501
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome methylation analyses of schizophrenia patients before and after treatment

Abstract: The aetiology of schizophrenia is still unknown but it involves both heritable and non-heritable factors. DNA methylation is an inheritable epigenetic modification that stably alters gene expression. It takes part in the regulation of neurodevelopment and may be a contributing factor to the pathogenesis of brain diseases. It was found that many of the antipsychotic drugs may lead to epigenetic modifications. We have performed 42 high-resolution genome-wide methylation array analyses to determine the methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
25
1
Order By: Relevance
“…Her performance was the worst of all 160 patients in this study (see Meltzer et al. 2014 for group data) . However, testing showed partial improvement beginning at the first retest week 6 of treatment starting oral risperidone and LAIR, with continuation of citalopram and carbamazepine (Figure ).…”
Section: Case Presentationmentioning
confidence: 71%
See 2 more Smart Citations
“…Her performance was the worst of all 160 patients in this study (see Meltzer et al. 2014 for group data) . However, testing showed partial improvement beginning at the first retest week 6 of treatment starting oral risperidone and LAIR, with continuation of citalopram and carbamazepine (Figure ).…”
Section: Case Presentationmentioning
confidence: 71%
“…Little is known about what enables prolonged remission in psychotic disorders. It may be related to disease modification based on changes in gene expression during aging, including epigenetic processes, psychotropic medications, other types of somatic treatments, effective psychotherapy, diminished stress, and many other factors . While remission in schizophrenia has occurred with APD treatment, it has also been suggested that APDs may damage neurons, interneurons, or glia, and, thus, be a contributor to poor outcome .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our systematic review yielded 29 studies (Table 1). Eighteen studies analyzed methylation in patients with schizophrenia, four studies in patients with bipolar disorder, and seven studies in a combined sample of patients with schizophrenia and bipolar disorder. The majority (n=22) of studies included observational sampling, such as cross‐sectional or case‐control studies, and the remaining analyzed changes in a prospective manner.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly employed measurement utilized restriction enzymes (five studies) followed by transposable elements (two studies) and ELISA (one study). 26 Obs 133 SCZ AAP and TAP Blood Global Cheng et al 27 Obs and prosp 30 Obs 172 BD olanzapine and quetiapine Blood d EWAS and genespecific Kinoshita et al 31 Prosp 21 SCZ olanzapine Blood EWAS Li et al 32 Obs 92 SCZ; 99 BD; 92 HC AAP and TAP Blood global Lott et al 33 Obs 85 SCZ NR blood gene-specific Melas et al 34 Obs 177 SCZ; 171 HC AAP and TAP Blood Global and genespecific Mill et al 35 Obs 35 SZ; 35 BD; 35 HC NR Brain EWAS Miura et al 36 Prosp 34 SCZ risperidone Blood Gene-specific Moons et al 37 Obs 438 SCZ AAP and TAP Blood Gene-specific Nour El Huda et al 38 Obs 138 SCZ; 132 HC AAP and TAP Blood Gene-specific Rukova et al 39 Prosp 20 SCZ; 220 HC NR Blood EWAS Shi et al 40 Prosp 288 SCZ risperidone Blood Gene-specific Swathy et al 41 Obs 184 SCZ; 330 HC NR Blood Global Tang et al 42 Prosp 82 SCZ AAP and TAP Blood Gene-specific Venugopal et al 43 Prosp 47 SCZ; 47 HC AAP Blood Gene-specific Zong et al 44 Obs 279 SCZ; 265 HC AAP and TAP Blood Gene-specific Details of 29 studies included in the systematic review including study design, type of antipsychotic within study, sample type for DNA methylation analysis, and overall DNA methylation strategy. AAP = atypical antipsychotic; BD = bipolar disorder; HC = healthy control; MDD = major depressive disorder; NR = not reported; obs = observational; PR = primary relative; pros = prospective; scz = schizophrenia; TAP = typical antipsychotic; UPR = unaffected primary relative.…”
Section: Global Methylation Studiesmentioning
confidence: 99%